Structural body and fireproof polymer cement mortar

A fire-resistant polymer cement mortar composition balances fire resistance and moldability by using specific resins and aggregates, enabling effective repair of concrete structures with neat corner formation.

JP2025017144APending Publication Date: 2025-02-05KONISHI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023120056
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Existing polymer cement mortar compositions lack both fire resistance and the ability to form neat, well-defined corners and edges, limiting their application in repairing concrete structures.

Method used

A fire-resistant polymer cement mortar composition is developed, combining specific types of resin, hollow-like thinned aggregates, and water-resistant cement, with controlled resin and aggregate content, to balance fire resistance and moldability.

Benefits of technology

The composition provides fire-resistant hardened products that can be easily molded to form neat corners and edges without frames, expanding its application in repairing concrete structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017144000001_ABST
    Figure 2025017144000001_ABST
Patent Text Reader

Abstract

To provide a polymer cement mortar capable of achieving both good angular moldability and fire resistance, and to provide a structural body containing the same.SOLUTION: A structural body comprises a concrete and a hardened fireproof polymer cement mortar, wherein the hardened fireproof polymer cement mortar comprises: a cement hydrate; a hollow fine aggregate; and a resin formed by polymerizing one or more selected from the group consisting of vinyl acetate, vinyl versatic acid, acrylic ester, and methacrylic ester.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fire-resistant polymer cement mortar composition, a structure containing the fire-resistant polymer cement mortar cured product, and a method for producing a structure using the fire-resistant polymer cement mortar composition. [Background technology]

[0002] When repairing the cross sections of concrete structures, there is a demand for repair materials with good corner formability that can be filled by hand and corners can be easily formed with a trowel or other tool. As such a repair material, as disclosed in Patent Document 1, a mixture of a polymer cement mortar composition having corner formability and water is used. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-8421 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the hardened product formed using the polymer cement mortar composition described in Patent Document 1 does not have fire resistance and has limited applications. On the other hand, there are also polymer cement mortar compositions capable of forming hardened products having fire resistance, but the mixture obtained by mixing this polymer cement mortar composition with water has a problem of lacking corner formability and insufficient workability.

[0005] The present invention was completed only after the inventors, who conducted intensive research to solve this problem, discovered that a polymer cement mortar composition that can achieve both good corner formability and fire resistance can be produced by using a specific combination of the type of polymer and the type of filler used. [Means for solving the problem]

[0006] That is, the structure, the refractory polymer cement mortar composition, and the method for producing the structure according to the present invention are as follows. [1] A structure comprising a concrete structure and a hardened fire-resistant polymer cement mortar, wherein the hardened fire-resistant polymer cement mortar contains cement hydrate, hollow fine aggregate, and a resin obtained by polymerizing one or more resins selected from the group consisting of vinyl acetate, vinyl versatate, acrylic acid esters, and methacrylic acid esters. [2] The structure according to [1], wherein the content of the hollow fine aggregate in the hardened fire-resistant polymer cement mortar is 10% by mass or more and 50% by mass or less. [3] The structure according to [1] or [2], wherein the content of the resin in the hardened fireproof polymer cement mortar is 0.5% by mass or more and 10% by mass or less. [4] The structure according to any one of [1] to [3], wherein the hollow fine aggregate has an average particle size of 75 μm or more and 600 μm or less. [5] The structure according to any one of [1] to [4], wherein the hollow fine aggregate is fly ash balloons. [6] The structure according to any one of [1] to [5], wherein the refractory polymer cement mortar further contains vinylon fiber. [7] A fire-resistant polymer cement mortar composition comprising hydraulic cement, hollow fine aggregate, and a resin obtained by polymerizing one or more compounds selected from the group consisting of vinyl acetate, vinyl versatate, acrylic acid esters, and methacrylic acid esters. [8] A refractory polymer cement mortar mixture comprising the refractory polymer cement mortar composition according to [7] and water, wherein the refractory polymer cement mortar has a flow value of 100 mm or more and 120 mm or less. [9] A method for producing a structure using a concrete structure and a fire-resistant polymer cement mortar composition, characterized in that the fire-resistant polymer cement mortar composition contains hydraulic cement, hollow fine aggregate, a resin obtained by polymerizing one or more resins selected from the group consisting of vinyl acetate, vinyl versatate, acrylic acid esters, and methacrylic acid esters, and water. Effect of the Invention

[0007] According to the present invention, it is possible to provide a polymer cement mortar composition which is capable of achieving both good corner formability and fire resistance. According to such a fire-resistant polymer cement mortar composition, even though it is a fire-resistant polymer cement mortar composition, for example, even when repairing a recess or a defect formed in a concrete structure, it is possible to form a neat corner by hand without using a formwork, and therefore the applications of the polymer cement mortar composition can be further expanded. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram of a structure including a hardened refractory polymer cement mortar according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The refractory polymer cement mortar composition according to the present embodiment is, for example, as follows.

[0010] The fireproof polymer cement mortar composition according to the present embodiment contains hydraulic cement, fine aggregate, and resin, and a fireproof polymer cement mortar mixture can be obtained by adding water to the fireproof polymer cement mortar composition and mixing it. Furthermore, the hydraulic cement and water in the fireproof polymer cement mortar mixture react with each other, and the hydraulic cement is hydrated to obtain a fireproof polymer cement mortar hardened material. Here, fireproof refers to states I to III in the explosion resistance test using a small fireproof furnace described later.

[0011] The hydraulic cement may be any known one that has been conventionally used to obtain mortar. For example, ordinary Portland cement, high-early-strength Portland cement, ultra-high-early-strength Portland cement, moderate-heat Portland cement, low-heat Portland cement, sulfate-resistant Portland cement, etc., as specified in JIS R 5210 (Portland cement); Examples of hydraulic cement that can be used include blast furnace cement as specified in JIS R 5211 (blast furnace cement), silica cement as specified in JIS R 5212 (silica cement), fly ash cement as specified in JIS R 5213 (fly ash cement), ecocement, normal ecocement, rapid hardening ecocement, etc. as specified in JIS R 5214 (ecocement), alumina cement, etc. These hydraulic cements may be used alone or in combination.

[0012] The fine aggregate includes hollow fine aggregate. Examples of hollow fine aggregate that can be used include fly ash balloons, shirasu balloons, glass balloons, resin balloons, volcanic ash soil, mesalite, asanolite, etc. Examples of hollow fine aggregate that can be used include East Spheres SLG, East Spheres SL150, East Spheres SL300, and Pozospheres 600 manufactured by Pacific Cement Corporation, and Hardlite B04 manufactured by Showa Chemical Industry Co., Ltd.

[0013] The average particle size of the fine aggregate is preferably 75 μm or more and 600 μm or less, more preferably 80 μm or more and 400 μm or less, and further preferably 100 μm or more and 350 μm or less. Since the use of hollow fine aggregate with a light specific gravity reduces the weight of the fireproof polymer cement mortar composition and makes the fireproof polymer cement mortar composition less likely to sag due to its own weight, it is preferable to use hollow fine aggregate with a specific gravity (bulk specific gravity) of about 0.6 or less. The specific gravity of the entire fireproof polymer cement mortar hardened product is preferably less than 1.4, and more preferably less than 1.1.

[0014] The content of fine aggregate in the fireproof polymer cement mortar composition or in the hardened fireproof polymer cement mortar product is preferably 10% by mass or more and 70% by mass or less, and more preferably 20% by mass or more and 60% by mass or less, when the entire fireproof polymer cement mortar composition or the hardened fireproof polymer cement mortar product is taken as 100% by mass.

[0015] By setting the fine aggregate content in the fireproof polymer cement mortar composition or in the hardened fireproof polymer cement mortar product to 10% by mass or more, it is possible to suppress sagging of the resulting fireproof polymer cement mortar mixture. By setting the fine aggregate content in the fireproof polymer cement mortar composition or in the hardened fireproof polymer cement mortar product to 70% by mass or less, it is possible to suppress the resulting fireproof polymer cement mortar mixture from becoming dry, improving workability, and also to obtain sufficient strength in the hardened fireproof polymer cement mortar product.

[0016] The fine aggregate may contain solid fine aggregate, but the content of hollow fine aggregate in the total fine aggregate is preferably 50% by mass or more, more preferably 65% ​​by mass or more, and particularly preferably 80% by mass or more. The fine aggregate may be only hollow fine aggregate. The content of hollow fine aggregate in the fireproof polymer cement mortar composition or in the hardened fireproof polymer cement mortar product is preferably 10% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 45% by mass or less, when the entire fireproof polymer cement mortar composition or the hardened fireproof polymer cement mortar product is taken as 100% by mass.

[0017] The resin contains a polymer obtained by polymerizing or copolymerizing one or more selected from the group consisting of vinyl acetate, vinyl versatate, acrylic acid ester, and methacrylic acid ester. The resin may contain a polymer other than the above-mentioned polymers, but it is preferable that the resin is made of the above-mentioned polymers. Specific examples of the polymer include vinyl acetate-vinyl versatate, vinyl acetate-vinyl versatate-acrylic, ethylene vinyl acetate, acrylic, and the like.

[0018] Examples of resins that can be used include Mowinyl Powder DM2072P, Mowinyl Powder DM201P, Mowinyl Powder DM2077P, Mowinyl Powder DM1645P, and Mowinyl Powder DM7000P, all of which are manufactured by Japan Coating Resins Co., Ltd.

[0019] The content of the resin in the fireproof polymer cement mortar composition or in the hardened fireproof polymer cement mortar product is preferably 0.5% by mass or more and 10% by mass or less, more preferably 1% by mass or more and 10% by mass or less, and particularly preferably 2% by mass or more and 6% by mass or less, when the entire fireproof polymer cement mortar composition or the hardened fireproof polymer cement mortar product is taken as 100% by mass.

[0020] Water is added to make the refractory polymer cement mortar mixture easier to handle and to hydrate the hydraulic cement, but in order to prevent the refractory polymer cement mortar mixture from becoming too fluid, which causes sagging, or from becoming too fluid, which causes poor moldability, it is preferable to set the mass ratio of hydraulic cement to water in the refractory polymer cement mortar mixture (water / hydraulic cement) to 0.3 or more and 0.6 or less. By setting these mass ratios to 0.3 or more, not only can the mixture be prevented from becoming dry and difficult to work with, but also the amount of water required for the hydration reaction of the hydraulic cement can be secured, and the physical properties required for the hardened refractory polymer cement mortar obtained by hardening the mixture can be imparted to the hardened refractory polymer cement mortar. In addition, by setting these mass ratios to 0.6 or less, not only can the sagging of the refractory polymer cement mortar mixture be prevented, but also the physical properties required for the hardened refractory polymer cement mortar can be obtained.

[0021] The fire-resistant polymer cement mortar composition, mixture and hardened product may contain various additives in addition to those mentioned above. Examples of the additives include water retention agents (thickeners), chemical admixtures, mineral admixtures, short fibers, antifoaming agents, retarders, and the like.

[0022] Examples of water-retaining agents that can be used alone or in combination include cellulose derivatives such as methylcellulose (MC), hydroxypropyl methylcellulose (HPMC), hydroxyethyl methylcellulose (HEMC), methylhydroxyethyl cellulose (MHEC), methylhydroxypropyl cellulose (MHPC), and hydroxyethyl cellulose (HEC); modified polysaccharides; hydroxypropyl guar gum derivatives; acrylic thickeners such as sodium polyacrylate, polyacrylamide, and partially sulfonated polyacrylamide; and water-soluble polymers such as curdlan, welan gum, and polyvinyl alcohol (PVA).

[0023] As the chemical admixture, an air-entraining agent, a water-reducing agent, an air-entraining water-reducing agent, a high-performance water-reducing agent, etc., as specified in JIS A 6204 (chemical admixtures for concrete) can be used.

[0024] Examples of mineral admixtures that can be used include fly ash as specified in JIS A 6201 (fly ash for concrete); ground granulated blast furnace slag as specified in JIS A 6202 (ground granulated blast furnace slag for concrete); and silica fume as specified in JIS A 6207 (silica fume for concrete).

[0025] Examples of the short fibers include vinylon fibers, nylon fibers, polyethylene fibers, and polypropylene fibers. Examples of the defoaming agent include polyether-based defoaming agents, silicone-based defoaming agents, and higher alcohol-based defoaming agents. Examples of retarders that delay the setting of hydraulic cement include sodium gluconate, potassium gluconate, calcium gluconate, sodium citrate, potassium citrate, calcium citrate, sodium tartrate, potassium tartrate, and calcium tartrate. It should be noted that the above-mentioned additives are not essential components, and even without using these substances, it is possible to obtain a fireproof polymer cement mortar composition, mixture, and hardened product that is free of sagging, has good workability, and has sufficient fire resistance.

[0026] The fireproof polymer cement mortar composition according to the present embodiment can be obtained by appropriately mixing the above-mentioned components in a mass ratio. The order of mixing may be any. The method of preparing a fireproof polymer cement mortar mixture using the fireproof polymer cement mortar composition is not particularly limited, and for example, water may be added to a powder composition containing hydraulic cement, fine aggregate, and resin. The resin may be dissolved or dispersed in water in advance, and the water may be added and mixed with a powder composition containing hydraulic cement and fine aggregate to prepare a fireproof polymer cement mortar mixture.

[0027] As described above, the fireproof polymer cement mortar composition and mixture according to the present embodiment harden as a result of hydration of the hydraulic cement and a portion of the water, and the water not used in the hydration reaction evaporates to become a fireproof polymer cement mortar hardened product, which exerts its strength. For example, as shown in FIG. 1, the fireproof polymer cement mortar composition and mixture can form a structure together with an existing concrete structure.

[0028] The fireproof polymer cement mortar composition and / or mixture according to the present embodiment can be used in the same manner as the mortar composition or mixture used for repairing the cross section of a conventional concrete structure, for example. Specifically, the fireproof polymer cement mortar mixture is filled into cracks, chips, and other defects in the concrete of a reinforced concrete structure. This filling may be done by hand or with a trowel. For example, the fireproof polymer cement mortar mixture may be packed into a ball and filled all at once, or the fireproof polymer cement mortar mixture may be applied in succession.

[0029] If necessary, in order to improve the adhesion between the concrete structure and the fireproof polymer cement mortar mixture and / or the hardened product, a primer may be applied to the concrete surface in advance to form a primer layer between the concrete structure and the fireproof polymer cement mortar mixture and / or the hardened product. Primers include emulsion-based primers and epoxy resin-based primers, and it is preferable to use an epoxy resin-based primer in order to improve adhesion. The fireproof polymer cement mortar composition according to the present embodiment can be used not only for repairing the cross-section of the reinforced concrete structure as described above, but also for producing a new structure containing a concrete structure and a hardened fireproof polymer cement mortar product, and can be widely used for various purposes.

[0030] The fireproof polymer cement mortar mixture according to the present embodiment has almost no fluidity and does not sag, and the flow value is preferably in the range of 100 mm to 120 mm, more preferably in the range of 105 mm to 115 mm. Here, the flow value is a value obtained based on the flow test described in JIS R 5201 (physical test method for cement) 11. Here, the flow value was measured using a sample obtained by mixing and stirring the fireproof polymer cement mortar composition and water, and leaving it to stand for 10 minutes. A flow value of 100 mm means that the mixture does not show any fluidity. If the flow value exceeds 120 mm, sagging is likely to occur. If the fireproof polymer cement mortar mixture has a flow value in the range of 100 mm to 120 mm, it has almost no fluidity and can be expressed as non-fluidity.

[0031] As described above, the refractory polymer cement mortar mixture according to the present embodiment has low fluidity, so it can be filled by hand and has excellent workability. After filling, the surface of the refractory polymer cement mortar mixture can be smoothed with a trowel or by hand. Although the refractory polymer cement mortar mixture according to the present invention has low fluidity, it can be easily smoothed with a trowel or by hand, and when corners are to be formed, it is possible to easily and neatly form the corners by simply shaping with a trowel or by hand.

[0032] The present invention is not limited to the above-described embodiment, and various modifications and combinations of the embodiments may be made without departing from the spirit of the present invention. EXAMPLES

[0033] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these.

[0034] <Preparation of refractory polymer cement mortar compositions and mixtures> A polymer cement mortar composition having the composition shown in Table 1 below was prepared, and water in the amount shown in Table 1 was further added to obtain a polymer cement mortar mixture (test mortar). All values ​​in Table 1 that do not have a specific unit are in grams (g). Table 2 shows the names and manufacturers of each component used in Table 1.

[0035] [Table 1]

[0036] [Table 2]

[0037] The performance of the polymer cement mortar compositions of the examples and comparative examples shown in Table 1, mixtures (test mortars) obtained by adding water to these compositions, and hardened products (test specimens) obtained by hardening these compositions were evaluated by conducting the following experiments, and the results are shown in Tables 1 and 3. <(Water / hydraulic cement) mass ratio> The mass ratio of water to hydraulic cement in the test mortar was calculated.

[0038] <Fine aggregate ratio in hardened material / Hollow fine aggregate ratio in hardened material / Resin ratio in hardened material> The test mortar was molded into a size of 40 mm length x 40 mm width x 160 mm height, and then cured for 28 days at 20°C and 60% humidity to obtain a test specimen. The weight of the test mortar immediately after molding and the test specimen after 28 days of curing were measured, and the difference between the weights was considered to be the amount of water that was evaporated without being used in the hydration reaction, and the amount of water contained in the hardened product was calculated. Since the powder components other than water are the same in the composition and the hardened product, the calculated amount of water in the hardened product was used to calculate the mass% of the fine aggregate, hollow fine aggregate, and resin when the entire hardened product is taken as 100 mass%, and the results are shown in Table 1.

[0039] <Explosion resistance test (fire resistance test)> At a temperature of 20°C and humidity of 60%, an epoxy resin primer (Bond Uni-Epoxy Repair Primer, manufactured by Konishi Co., Ltd.) was applied to a 30 cm x 30 cm x 6 cm concrete slab (application amount: 300 g / m 2 ), and after 30 minutes of curing, the test mortar of the embodiment or comparative example was applied in a thickness of 3 cm, finished with a trowel, and cured for 28 days to prepare a test specimen. A spalling prevention layer (mesh layer) was placed at a depth of 1 cm from the trowel-finished surface of the test mortar. The test specimen was placed in a small fireproof furnace and heated for one hour according to the ISO standard heating curve. After the heating was completed, the test specimen was removed from the furnace when the temperature inside the furnace became 200°C or less, and the damage state was observed and classified according to the following criteria. In addition, if the test is in the state I to III, it can be judged that the specimen has fire resistance. In addition, this test was performed based on the explosive spalling test described in No. 147 of "Building Research Report" published by the Building Research Institute, "Study on Ensuring Cover Thickness of Reinforced Concrete Buildings," written by Hamasaki Hitoshi et al. (2013). Condition I: Cracks have occurred but there is no spalling or cracking. Condition II: There was no explosion, and only partial peeling occurred on the surface layer of the anti-fall mesh. Condition III: Partial spalling and cracking occurred only on the surface. Condition IV: The inside of the container has partially exploded due to the mesh used to prevent the container from falling off. Condition V: The inside of the item has exploded due to the mesh preventing it from falling off almost entirely.

[0040] <Workability 1: Ease of handling by hand> The test mortar was collected and collected by hand, and the ease of application when filling defects in concrete structures was evaluated using the following four-point scale. ◎: The test mortar could be easily clumped together by hand and was easy to apply. Good: The test mortar was slightly dry but workable. △: The test mortar got a little on the hands and was difficult to apply, but work was possible. ×: The test mortar could not be scooped up by hand. It was sticky and could not be spread on the hands, making application impossible.

[0041] <Workability 2: Paintability> To increase the thickness, the adhesiveness of the test mortar when filling multiple layers was evaluated using the following four-point scale. ◎: No peeling occurred on the joint surfaces of the test mortar, and two layers were easily applied to a thickness of about 5 cm. ○: The test mortar could be applied with slight vibration or force. △: The test mortar could not be jointed, but it was possible to joint the mortar by applying water or a primer to the joint interface or by applying vibration or force. ×: The test mortar could not be applied.

[0042] <Workability 3: Ease of use with trowel> After the test mortar was filled, the surface was smoothed with a trowel and the ease of smoothing was evaluated according to the following four-point scale. ⊚: The test mortar did not easily adhere to the trowel, was easy to level, and was possible to mold. ◯: Although the test mortar adhered slightly to the trowel, it was easy to level and mold by lightly cleaning the trowel. △: A small amount of the test mortar adhered to the trowel, and it took time and effort to level and shape it. ×: The test mortar adhered to the trowel, making it difficult to smooth and shape.

[0043] <Workability 4: Corner molding and resistance to sagging> The test mortar was applied to a concrete slab measuring 10cm length x 10cm width x 3cm thickness, and the concrete slab was then stood vertically. The test mortar was left to cure for one day at a temperature of 23°C and humidity of 50%, after which the formability of the corner and the displacement of the apex of the corner after curing for one day were measured, and the sagging was evaluated on the following four-point scale. ⊚: The corner was easily molded, and the displacement of the apex of the corner after hardening was 0 mm. ◯: The corners were easy to form, and the displacement of the apex of the corners after hardening was within 2 mm. △: It was difficult to mold the corners. (It was possible to mold the corners, but it was time-consuming.) ×: Corner corners could not be formed.

[0044] [Flow value] The test mortar was measured based on the flow test described in 12 of JIS R 5201 (physical test method for cement). [Flexural strength test and compressive strength test] The bending strength and compressive strength of the specimens were measured according to the description of JIS A 1171. That is, the test mortar was molded into a size of 40 mm length x 40 mm width x 160 mm height, and then subjected to 2 days of moist air curing at 20°C and 90% humidity. After that, the specimens were subjected to 26 days of dry curing at 20°C and 60% humidity to obtain the specimens. The bending strength (N / mm 2 ) and compressive strength (N / mm 2 ) was measured.

[0045] [Apparent Density] The test mortar was molded into a size of 40 mm length x 40 mm width x 160 mm height, and then cured for 28 days at 20°C and 60% humidity to obtain a hardened polymer cement mortar (specimen). The apparent density of the specimen was calculated using the following formula. Apparent density (g / cm 3 ) = mass of specimen (g) / volume of specimen (cm 3 )

[0046] [Table 3]

[0047] <Considerations on Examples and Comparative Examples> The results in Table 1 show that the combination of hollow fine aggregate and a specific resin made it possible to obtain a hardened product with sufficient fire resistance in Examples 1 to 10. The results in Table 3 show that the fire-resistant polymer cement mortar mixtures according to these Examples not only had sufficient corner formability but also other workability.

[0048] In addition, in Examples 1 to 10 in Table 1, the mass ratio of (resin / hydraulic cement) is 0.1, but as a result of carrying out experiments in which the mass ratio is changed from 0.05 to 0.15 for each type of resin, it has been confirmed that a cured product exhibiting high fire resistance can be obtained when the mass ratio of (resin / hydraulic cement) is in the range of 0.05 to 0.15. More specifically, when DM201P or DM2077P is used as the resin, it has been found that the cured product exhibits high fire resistance when the mass ratio of (resin / hydraulic cement) is in the range of 0.05 to 0.15. When DM2072P is used as the resin, it has been found that a cured product exhibiting higher fire resistance can be obtained when the mass ratio of (resin / hydraulic cement) is 0.05 than when it is 0.1 or more. When DM7000P is used as the resin, it has been found that a cured product exhibiting higher fire resistance can be obtained when the mass ratio of (resin / hydraulic cement) is in the range of 0.05 to 0.10 than when it is 0.15 or more.

[0049] On the other hand, in Comparative Example 1, which used hollow fine aggregate as the fine aggregate but SBR as the resin, and in Comparative Example 2, which used vinyl acetate-vinyl versatate-acrylic as in the examples but only used sand, which is a solid fine aggregate, as the fine aggregate, no fire resistance was demonstrated at all.

Claims

1. A structure comprising a concrete structure and a hardened refractory polymer cement mortar, the hardened refractory polymer cement mortar comprising: Cement hydrate; Hollow fine aggregate; and a resin obtained by polymerizing one or more members selected from the group consisting of vinyl acetate, vinyl versatate, acrylic acid esters, and methacrylic acid esters.

2. 2. The structure according to claim 1, wherein the content of the hollow fine aggregate in the hardened fireproof polymer cement mortar is 10% by mass or more and 50% by mass or less.

3. 2. The structure according to claim 1, wherein the content of the resin in the hardened fireproof polymer cement mortar is 0.5% by mass or more and 10% by mass or less.

4. 2. The structure according to claim 1, wherein the hollow fine aggregate has an average particle size of 75 μm or more and 600 μm or less.

5. The structure of claim 1 , wherein said hollow fine aggregate is fly ash balloons.

6. 10. The structure of claim 1, wherein the cured fire-resistant polymer cement mortar further comprises vinylon fiber.

7. Hydraulic cement; Hollow fine aggregate; a resin obtained by polymerizing one or more members selected from the group consisting of vinyl acetate, vinyl versatate, acrylic acid esters, and methacrylic acid esters; A fire-resistant polymer cement mortar composition comprising:

8. A refractory polymer cement mortar mixture comprising the refractory polymer cement mortar composition of claim 7 and water, A fire-resistant polymer cement mortar mixture having a flow value of 100 mm or more and 120 mm or less.

9. A method for producing a structure using a concrete structure and a fire-resistant polymer cement mortar composition, comprising the steps of: The refractory polymer cement mortar composition comprises: Hydraulic cement; Hollow fine aggregate; and a resin obtained by polymerizing one or more members selected from the group consisting of vinyl acetate, vinyl versatate, acrylic acid esters, and methacrylic acid esters.

Citation Information

Patent Citations

  • Non-fluidity mortar composition for cross-sectional repair

    JP2006008421A